Effect of potassium deficiency on the magnesium metabolism of rats - ZHENG Guo-ji; DING Yan-yan; XU Ye; QIAN Shao-zhen (Acta Pharmacologica Sinica, 2016)
Rats fed low-k feed for 20 d showed decrease in serum K concentration and intracellular K concentration of the skeletal muscle, together with a marked increase in serum Mg concentration. No significant alterations were seen either in the intracellular Mg concentration or in the volumes of the intraand extracellular spaces of the skeletal muscles. Results indicate that in K-deficient rat, there is no change in the celluar content of Mg; the elevation of serum Mg concentration may be the consequence of increased intestinal absorption and/or decreased urinary excretion of Mg.